Evaluasi Situs Web Pemerintah Menggunakan Metode Webqual Dan Importance-Performance Analysis (IPA) (Studi Kasus: Situs Kecamatan Lowokwaru-Malang) - Liyan Nasution; Ismiarta Aknuranda; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The Internet in government gives positive influence to performance in support of good governance. Lowokwaru sub-district site as reference's society in getting all information, so this site must be able to present of professional sites and good quality be based on user's perception by conducting an evaluation. Evaluation of the site using WebQual 4.0 and Importance-Performance Analysis(IPA) method. The WebQual 4.0 as questionnaire have three dimension like usability, information quality, and quality of interaction. While IPA as analysis of the level suitability, gap analysis, and analysis of quadrant. The result from evaluation that the quality has a suitability of 99.43% which the respondent felt approaching satisfaction with the sites service. The result of gap analysis is -0.026, which respondent felt that quality of performance is low and can not meet the importance. On quadrant analysis show one attribute on the first quadrant, twelve attributes on the second quadrant, eight attributes in the third quadrant, one attribute on the fourth quadrant.